PENGARUH PEMBERIAN JERAMI PADI TERHADAP PERTUMBUHAN TANAMAN PADI (Oryza sativa) DI TANAH SULFAT MASAM - Arifin Fahmi (Research Center for Biology-Indonesian Institute of Sciences, 2010)
The objective of the experiment was to investigate the effect of rice straw application on the growth of rice in two conditions of acid sulphate soils. An experiment was conducted in the glass house consisting of three treatment factors using the completely randomized design with three replications.The first factor was soil condition consisting of continuous application of rice straw and without application of rice straw during the last 5 years. The second factor was fresh application of rice straw consisting of application and without application, whereas the third factor was P application consisting of 3 rates of SP - 36 fertilizers.Parameters measured were plant height, tiller number and Fe toxicity score. Measurement were conducted at 2, 4, 6 and 8 weeks after planting. Plant dry weight and P concentration in plant tissue were determined at 8 weeks after planting. The result showed the main effect of rice straw application was significant decrease on the tiller number of the rice plant at 2, 4 and 6 weeks after planting, whereas significant on plant height was observed at 2 and 4 weeks after planting. Based on the scoring of degree of Fe toxicity, it was concluded that the rice plant did not exhibit any effect of Fe toxicity.